Ulcer dermatitis in bovine caused by Stephanofilaria spp. - Novaes, Antonio Pereira de; Costa, Agnaldo José dos Santos; Barbosa, Rogério Taveira; Moreira, Danilo de Paula; Ruzza, Francisco José de (Pesquisa Agropecuaria Brasileira, 2014)
In a dairy cattle herd located at São Carlos, State of São Paulo, Brazil, five cases of ulcer dermatitis were observed and the ethiological agent identified as Stephanofilaria spp. The lesions were found at the tailhead, udder, thigh and rump. The diagnosis was done by scrapings and imprints obtained from both scratching and skin of the ulcer edge, stained with Giemsa and also with Congo red, the latter allowing better visualization of the parasite. The cure was obtained with triclorfon in a period of fifteen days.